The Influence of Service Performance Capabilities, Service Encounter, and Storynomics Tourism on Customer Delight Mediated by Memorable Tourism Experiences - Ari Yuniarso; Bahtiar Usman; Justine Tanuwijaya (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study examines the influence of service performance capabilities, service encounters, and storynomics tourism on customer delight, with memorable tourism experiences acting as a mediating variable. Grounded in the view that emotionally meaningful tourism experiences extend beyond conventional satisfaction, this explanatory study was conducted in Madiun City, East Java, Indonesia. Data were collected from 250 tourists using structured questionnaires measured on a five-point Likert scale and analyzed using Structural Equation Modelling–Partial Least Squares (SEM-PLS). The results indicate that service performance capabilities and storynomics tourism do not have a significant direct effect on customer delight, but both significantly enhance memorable tourism experiences. In contrast, service encounters exert a significant direct influence on both memorable tourism experiences and customer delight. Furthermore, memorable tourism experiences have a strong positive effect on customer delight and fully mediate the relationships between service-related variables and customer delight. The findings show that service performance capabilities (O = 0.032, p = 0.586) and storynomics tourism (O = 0.076, p = 0.197) do not have a significant direct effect on customer delight, although both significantly enhance memorable tourism experiences (O = 0.439 and O = 0.360, respectively; p = 0.000). Service encounters, however, have a significant positive impact on both memorable tourism experiences (O = 0.287, p = 0.000) and customer delight (O = 0.164, p = 0.000). Memorable tourism experiences strongly predict customer delight (O = 0.446, p = 0.000) and fully mediate the effects of service-related variables. These findings underscore the strategic importance of experience-based value creation and provide empirical support for service-dominant logic within the tourism context.